EVALUASI KINERJA PEMELIHARAAN ASET BANGUNAN PABRIK BLOK A – 06 DI PT. KAWASAN BERIKAT NUSANTARA (PERSERO) - Pasya Faishal Aushoof; Nurlaila Fadjarwati; Mariah Rabiatul Qibtiyah (Pondasi, 2020)
AbstractPT. Kawasan Berikat Nusantara (Persero) owns the building assets of block factory A-06 with an area of 5,400 m² with the condition of the building does not undergo improvement (indcondition) so that the offer price is low and the cost of repair of the building is high. There is also a waiting time when repairs are made so that investors need to wait for repairs to be completed. In the know of the performance of asset maintenance in the building of Block factory A – 06 used Key Maintenance Performance Indicators (Muchiri, 2010) based on 2 working areas (dimensions) are Leading Indicators and Lagging Indicators. The method used in the study is a descriptive method with a quantitative approach through data collection techniques for both interviews and documentation studies. The result of maintenance performance evaluation of the building assets of block plant A – 06 is known that the maintenance has been done is not optimal. A recommendation to solve the problem is to make a replanning of the A – 06 block factory building asset maintenance system.Keywords: evaluation of asset maintenance performance, building asset, building, Key Maintenance Performance Indicators.AbstrakPT. Kawasan Berikat Nusantara (Persero) memiliki aset bangunan pabrik blok A – 06 dengan luas 5.400 m² dengan kondisi bangunan tidak mengalami perbaikan (indcondition) sehingga harga penawaran sewanya rendah dan biaya perbaikan bangunannya tinggi. Terdapat juga waktu tunggu saat perbaikan dilakukan sehingga investor perlu menunggu perbaikan diselesaikan. Dalam mengetahui kinerja pemeliharaan aset pada bangunan pabrik blok A – 06 digunakan Key Maintenance Performance Indicators (Muchiri, 2010) berdasarkan 2 area kerja (dimensi) yaitu Leading Indicators dan Lagging Indicators. Metode yang digunakan dalam penelitian yakni metode deskriptif dengan pendekatan kuantitatif melalui teknik pengumpulan data baik wawancara dan studi dokumentasi. Hasil evaluasi kinerja pemeliharaan aset bangunan pabrik blok A – 06 diketahui bahwa pemeliharaan yang telah dilakukan tidak optimal. Rekomendasi pemecahan masalahnya adalah dibuat perencanaan ulang sistem pemeliharaan aset bangunan pabrik blok A - 06.Kata Kunci : evaluasi kinerja pemeliharaan aset, aset bangunan, Key Maintenance Performance Indicators.